Density Functional Theory Investigations on the Geometric and Electronic Structures of 4–Azidomethyl–6–Isopropyl–2H–Chromen–2–One - Toh, Pek Lan; Meepripruk, Montha; Lee, Sin Ang; Sulaiman, Shukri; Mohamed Ibrahim, Mohamed Ismail (EDP Sciences, 2015)
We have employed first principle Density Functional Theory (DFT) investigations to study the physical and electronic properties of 4–Azidomethyl–6–isopropyl–2H–chromen–2–one, C13H13N3O2. Complete geometry optimization calculations were carried out to find local energy minimum of the molecular system using the B3LYP approach with a variety of basis sets. The optimized geometries were then used to determine the HOMO–LUMO gaps, Mulliken atomic charges, and others. Our calculation results show that the computed geometrical properties of C13H13N3O2 cluster model are in good agreement with the corresponding measured experimental value. The calculated energies obtained are close to each other using the B3LYP density functional method combined with a variety of basis sets. Furthermore, using B3LYP/6–31G** method, the oxygen–attached carbon, C2 atom has the highest positively charge, with the corresponding value of +0.59. For both oxygen atoms (O1 and O2), the calculated charge values obtained are about –0.52 and –0.46, respectively.